Roasted coffee oil (Coffea arabica): Characterization of fatty acids, qualification of aromatic compounds and quantification of caffeine content (Research, Society and Development, 2020)
The shelf life of a vegetable oil depends on some variables which includes cultivation, extraction, transport and, mainly, the storage of the grains. Oxidation processes are responsible for reducing the shelf life of lipids from raw materials. Among oxidation processes, rancidity is the main alteration that occurs, resulting in considerable changes in the final and sensory quality of vegetable oils and directly determines its shelf life. Auto-oxidation, thermal polymerization or thermal oxidation are also chemical changes that occur in vegetable oils, and these reactions are accelerated by poor storage conditions and heating. Roasted coffee oil is a product with extremely high added value, since its market value is much higher than the main raw material, coffee. Therefore, the objective of this study was to qualify and quantify the fatty acids present in coffee oil through gas chromatography, qualify the aromatic compounds and quantify and monitor the caffeine content during 12 months at different storage temperatures. In the analysis of aromatic compounds, it was possible to identify several compounds responsible for the aroma of coffee and the malonaldehyde compound, which is responsible for the rancid aroma in oils during storage, was not identified. The main fatty acids present in coffee oil are Linoleic, Palmitic, Stearic and Oleic acid. The oil showed an amount of caffeine, which remained constant over 12 months at both storage temperatures.